Is passion contagious in coach-athlete dyads? A dyadic exploration of the association between passion, affective and need-based experiences in individual sports - Fonteyn, Marieke; Haerens, Leen; Vansteenkiste, Maarten; Loeys, Tom (Frontiers in Psychology, 2024)
The Dualistic Model of Passion distinguishes between harmonious and obsessive passion, which are associated with athletes' and coaches' adjustments. Whereas prior research sampled either athletes or coaches, the present study used a dyadic approach to explore the bidirectional influence of passion on affective experiences in coaches and athletes. Using a cross-sectional dyadic design, 198 coachathlete dyads involved in an individual sport at different competition levels, reported on their passion, need-based, and affective experiences. Both actor effects (i.e., intrapersonal dynamics within athletes or coaches) and partner effects (i.e., interpersonal dynamics from coach to athlete and vice versa) were examined. Furthermore, dyadic mediation models were used to investigate the potential mediating role of need-based experiences in the association between passion and affective experiences. Results unveiled compelling evidence for actor effects, indicating that one's own harmonious passion was positively related to one's own more adaptive outcomes and negatively to one's own more maladaptive outcomes, whereas obsessive passion was positively related to maladaptive outcomes. Further, very limited evidence for partner effects, in which coaches' passion affected athletes' outcomes or vice versa, was found. The dyadic mediation models underscored the role of need-based experiences in mediating the association between passion and affective experiences, but only at the intrapersonal level. As such, one's own passion experiences were related to one's own need-based experiences, which in turn were related to one's own affective experiences. The study provided no evidence for interpersonal mediation effects.